The Analysis of Factors Affecting Unmet Need in Fertile Age Women in Sumberjambe District, Sumbersari, and Kaliwates - Latifah Hanum; Ancah Caesarina Marchianti; Ristya Widi Endah Yani (Health Notions, 2018)
Unmet need family planning is a need for contraception that is not met. Fertile age women are said to be unmet need family planning if they wish to delay pregnancy or to terminate pregnancy for the next two years but not to use contraceptives. The purpose of this study was to analyze the influence of predisposing factors, enabling factors, and reinforcing factors in fertile couple women in Sumberjambe, Sumbersari and Kaliwates. The research design used was observational analytic with cross sectional research design. Samples taken in this study were 382 women of fertile couples age. The sampling technique used was multistage random sampling technique. Data anaysis used logistic regression. The results showed that there was influence of predisposing factor, enabling factor and reinforcing factor to contraception that was not fulfilled in fertile age women of knowledge with value of (p = 0.000), attitude with value of (p = 0.000), access service with value of (p = 0.000), quality of service with value of (p = 0.002), husband support with value of (p = 0.000), family panning officer support with value of (p = 0.000), and IEC treatment with value of (p = 0.000). Keywords: knowledge; attitude; social culture; service access; quality of service